Conference on Lasers and Electro-Optics 2016
DOI: 10.1364/cleo_qels.2016.ftu4a.4
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Bunching in the Soliton Rain Regime of an Ultralong Fiber Laser Mediated by Forward Brillouin Scattering

Abstract: We present experimental evidence for soliton bunching mediated by forward Brillouin scattering in the soliton rain regime of an ultralong fiber laser. Spatio-temporal dynamics show an initial acceleration followed by self-organization of the rain solitons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Soliton rain was first found experimentally for a fiber laser, mode-locked using a nonlinear polarization rotation [10]. Then it was observed for the mode-locking techniques based on Brillouin scattering [11], a nonlinear amplified loop mirror or a figure of eight cavity [12,13]. It was also found that a high pump power of 430 mW is required for the observation of soliton rain in these lasers [9,13].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Soliton rain was first found experimentally for a fiber laser, mode-locked using a nonlinear polarization rotation [10]. Then it was observed for the mode-locking techniques based on Brillouin scattering [11], a nonlinear amplified loop mirror or a figure of eight cavity [12,13]. It was also found that a high pump power of 430 mW is required for the observation of soliton rain in these lasers [9,13].…”
Section: Introductionmentioning
confidence: 98%
“…A mode-locked fiber laser, acting as a source of femtosecond pulses with a high repetition rate of tens of megahertz, has fundamental technological importance in revolutionizing a wide range of natural and applied research areas [1][2][3][4]. The complex interplay of linear and nonlinear effects results in the diversity of nonlinear dynamic patterns; including soliton rain, which was systematically explored by controlling individual laser parameters, such as pump power, state of polarization (SOP) and cavity dispersion [5][6][7][8][9][10][11][12][13][14][15]. Soliton rain is a bunch of tens of small soliton pulses accompanying the main pulse and coexisting with a continuous wave (cw) background [9].…”
Section: Introductionmentioning
confidence: 99%
“…Our observations suggest the existence of the internal motions of the SR that have not been discovered yet, probably mediated by the ARs, besides the internal pulse bunching in the SR regime [22].…”
Section: Tailoring Of Mpd Via Optoacoustically Manipulated Qcwbmentioning
confidence: 52%
“…It has been recently demonstrated that the use of gigahertz ARs tightly confined in the micron-sized core of photonic crystal fiber can solve this issue, stabilizing the harmonically mode-locked pulse train at the repetition rate beyond 1 GHz [16][17][18]. The formation of pulse bunches and bound pulse states via the optoacoustic inter-pulse coupling has also been investigated [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%